Flowering behaviour of avocado (Persea americana) genotypes in humid tropical region of India - TRIPATHI, P C; KARUNAKARAN, G; SANKAR, V; JAYANTHIMALA, B R; SUNANDA, S (The Indian Journal of Agricultural Sciences, 2016)
A study on flowering and fruiting behaviour of 35 accessions of avocado (Persea americana Mill.) was carried out at CHES, Chettalli during 2013-14. The results revealed that number of panicles/shoot ranged from 2.6 in accession CHESPA-I-4 to 13.8 in accession CHESPA-XII-4. The panicle length ranged from 5.16 cm in CHESPA-IX-3 to 18.4 cm in CHESPA-VIII-3. The number of flowers/shoot ranged from 22.68 to 218.96. The panicles were produced on terminal bud and most of them were determinate type. The flowering period ranged from 27 to 53 days. The double opening of flowering was noticed in all the accessions. The accessions were classified in ‘A’ type and ‘B’ type on the basis of their flowering pattern. In ‘A’ type accessions, flowers open in the morning as female stage and reopen in the afternoon of the next day at the male stage. In the type ‘B’ accessions, the flowers open in the afternoon as female stage, close in the evening and reopen the following morning at the male stage. Out of 35 genotypes evaluated, 20 were ‘A’ type while 15 were ‘B’ type. The average initial fruit set was 3.62% and it was highest (8.74%) in CHESPAVIII- 3 and lowest (0.50%) in CHESPA-VI-1. Average final fruit set was 0.32%. Among the 35 accessions evaluated, all the fruits dropped in 24 accessions before attaining harvest maturity. The highest final fruit set (1.32%) was recorded in accession CHESPA-II-1. Heavy fruit drop was observed during various stages of fruit growth and development in majority of the accessions. This may be attributed to improper pollination and environmental conditions during growth and development of fruits. The results will be useful in identifying suitable combinations of elite lines.